(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
Putrajaya is a unique Malaysian city from a transport policy perspective because of its explicit goal to achieve a 70% share of public transport to its core areas. However, the current modal split between public transport and private transport is 15:85. One possible way to reduce the use of cars is to promote people to use public transport as a primary mode of transport. In order to evaluate the effects of this measure, data were collected from the workers who travel by car to work place in Putrajaya. A total of 290 respondents completed a questionnaire with a response rate of 58% (out of 500 distributed questionnaires). Logistic regression method has been used to analyze the factors that influence users to switch their trips mode to shift to public transport. It is concluded that with reducing the bus travel time and implementing parking fee will directly affect the use of the public transport facility.